Pricing Vulnerable Option under Jump-Diffusion Model with Incomplete Information - Yang Jiahui; Zhou Shengwu; Zhou Haitao; Guo Kaiqiang (Discrete Dynamics in Nature and Society)
In this paper, the closed-form pricing formula for the European vulnerable option with credit risk and jump risk under incomplete information was derived. Noise was introduced to the option writers assets while the underlying asset price and the value of corporation were assumed to follow the jump-diffusion processes. Finally the numerical experiment showed that jumps of underlying assets would increase the value of the option, but noise of corporation value was opposite.